Tradisi Mamat dalam membangun Relasi Sosial Keagamaan di Naikolan Provinsi Nusa Tenggara Timur - Nefriyanti Ema Penna (Mahesa Research Center, 2021)
This study aims to describe the understanding of the Evangelical Christian Church in the East regarding the hospitality contained tradition eating betel nut, especially next generation who will continue meaning of hospitality in tradition of mamat for daily life and use betel nut as a unifying tool and a sign of respect diversity congregation. Tradition eating betel nut is a symbol of hospitality in the tradition priest. Tradition of mamat provides a new understanding Evangelical Christian Church in the East of Mount Sinai that through betel nut is interpreted as a sign of love and hospitality to others both within the congregation and outside the church context. This research uses descriptive qualitative method. A qualitative approach that aims to accurately describe the characteristics individual, symptom, or group determine the causes frequency certain relationship between a symptom and other symptoms in society, so as obtain in-depth information through interviews with respondents. Mamat tradition also provides good change for the community, especially church because it can teach about mutual acceptance and respect regardless of status, tradition of eating betel nut together allows people have good behavior such as loving, appreciating, and respecting others. With the Mamat tradition, community mingled with each other without seeing any differences.This study aims to describe the understanding of the Evangelical Christian Church in the East regarding the hospitality contained tradition eating betel nut, especially next generation who will continue meaning of hospitality in tradition of mamat for daily life and use betel nut as a unifying tool and a sign of respect diversity congregation. Tradition eating betel nut is a symbol of hospitality in the tradition priest. Tradition of mamat provides a new understanding Evangelical Christian Church in the East of Mount Sinai that through betel nut is interpreted as a sign of love and hospitality to others both within the congregation and outside the church context. This research uses descriptive qualitative method. A qualitative approach that aims to accurately describe the characteristics individual, symptom, or group determine the causes frequency certain relationship between a symptom and other symptoms in society, so as obtain in-depth information through interviews with respondents. Mamat tradition also provides good change for the community, especially church because it can teach about mutual acceptance and respect regardless of status, tradition of eating betel nut together allows people have good behavior such as loving, appreciating, and respecting others. With the Mamat tradition, community mingled with each other without seeing any differences.Keywords: Mamat; Tradition; Betel Nut; Hospitality